Serum and follicular anti-Mullerian hormone levels in women with polycystic ovary syndrome (PCOS) under metformin - Falbo Angela; Rocca Morena; Russo Tiziana; D'Ettore Antonietta; Tolino Achille; Zullo Fulvio; Orio Francesco; Palomba Stefano (BMC, 2010)
Abstract Background No data regarding metformin effects on follicular fluid anti-Müllerian hormone (AMH) levels were to date available in literature. The aim of the present study was to evaluate in patients with polycystic ovary syndrome (PCOS) whether metformin administration affects serum and follicular AMH levels, and whether this is related to ovarian response to the treatment. Methods Twenty young patients with PCOS who had received metformin were enrolled. Ten patients were anovulatory (Met-anov group), whereas the other 10 were ovulatory (Met-ov group) but had failed to conceive. Further untreated PCOS (PCOS controls, n. 10) and healthy controls (non-PCOS controls, n. 10) who were scheduled for laparoscopic surgery were enrolled. In each subjects, clinical and biochemical evaluations were performed. AMH concentrations in blood and antral follicular fluid were assayed. Results In both Met-anov and Met-ov groups, and without difference between them, serum androgens and AMH, and indices of insulin resistance were significantly (p < 0.05) improved after treatment. On the other hand, significant differences (p < 0.05) between the two groups were detected with respect to the same biochemical parameters in antral follicular fluid. In the Met-anov group, no significant correlation was observed between AMH concentrations in the follicular fluid and variation in serum androgens, AMH and insulin resistance indexes; whereas in Met-ov group significant correlations were detected between AMH levels in the follicular fluid and variation in serum androgens, AMH and insulin resistance indexes. Conclusions Metformin administration in patients with PCOS exerts a differential action on the ovarian AMH levels on the basis of ovulatory response. Changes in AMH levels in antral follicular fluid during metformin treatment could be involved in the local mechanisms mediating the ovulatory restoration.